Pengaruh Struktur Modal Terhadap Kinerja Keuangan Perusahaan Consumer Goods Sub Sektor Rokok Yang Terdaftar di Bei - Yuniati Doti Allo; Jemi Pabisangan Tahirs; Dina Ramba (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the effect of capital structure on financial performance in consumer goods companies in the cigarette sub-sector listed on the IDX. Research data obtained by looking at the balance sheet and income statement of the consumer goods company for the period 2018-2022. The research method used in this research is quantitative research. The data analysis technique used in this study is multiple linear regression test with statistical calculation tools using SPSS version 25.0. The results of this study indicate that Debt to Asset simultaneously has no significant effect on Financial Performance Debt to Equity Ratio partially has no significant effect on Financial Performance. Time Interest Earned partially has a significant effect on Financial Performance. DAR, DER and TIE simultaneously have a significant effect on Financial Performance.